A generalized inelastic modeling concept for soft fibrous tissues. Issue 4 (14th May 2019) - Hillgärtner, Markus; Linka, Kevin; Itskov, Mikhail
Abstract : This contribution proposes a multiscale modeling approach, ranging from the macromolecular behavior of tropocollagen over collagen fibrils and the interfibrillar matrix up to bundles of collagen fibers. Two damage mechanisms are described: intramolecular damage inside the tropocollagen molecules based on a permanent opening of the triple helical conformation and damage in the interfibrillar matrix restricting the recovery of interfibrillar sliding. Both intramolecular and interfibrillar damage is considered as a probabilistic process based on detachment of adhesive bonds, where the probability of failure depends on the full load history of the bond. The presented modeling concept is based on generalized assumptions valid for most soft fibrous tissues, and can therefore be applied for a variety of tissues and load‐cases. The final constitutive equations are validated against recent experimental data from uniaxial tension tests of rat tail tendon. All utilized material constants have a clear physical interpretation.